Disaster management for the Philippine Supreme Court library - Nicerio, Jessel C.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
The term 'disaster' is quite ambiguous and can cover a wide range of events from minor incidents to grave emergencies. Disaster in the even best-run institutions can and do happen. Thus, preventive measures are very important not only for the affected areas but for every area that a calamity is calculated to hit and to be able to do that, the local people or the people inside each institution need to be educated to such possibility. This study aimed: To find out the kinds of hazards the library and its collections are exposed to in the circumstances where it is now; to discover the kinds of disasters and hazards the library has experienced since its rehabilitation from destruction due to the bombing of Manila during World War II and how it has coped with these incidents (i.e. if it coped adequately according to set standards such as that recommended by IFLA); and to propose the applicable disaster management and recovery program that can best meet the needs of the Library of the Supreme Court of the Philippines.
The qualitative method was employed in this study. Respondents were the Supreme Court's librarian and staff who were interviewed and asked to fill out a questionnaire on the risks faced by the collection and the building and what the library is doing to prepare for or prevent the happening of disasters.
Out of 36 declared Philippine Supreme Court library staff and librarians, only 16 (44.4) were able to respond. Based on responses to the questionnaire, it was found out that the Philippine Supreme Court library does not have its own disaster management plan apart from what the Supreme Court uses. The employees also generally do not know if they have such a plan or not. The study identified some potential hazards that can affect the library's collection. On top of the list is the risk of fire, followed by earthquake, then the potential risk of power failure, bomb threats and violent mass actions, water leaks and the potential danger of termites and rats.
The following conclusions were arrived at base on the findings of the study: There is no disaster management plan for the Supreme Court Library; the staff members are not all aware of the importance of a disaster management plan; the annual drill that the staff of the library experiences are all organized by the main disaster management team of the Supreme Court and it focuses on the Supreme Court as an institution; there are no individual training sessions for the sub-institutions such as the library that will show the staff how to take care of the collection; the Supreme Court library is receptive to having its own disaster management plan which caters not only to the building and building's safety but also to the collection.
The study recommends that the Philippine Supreme Court Library should have it's own Disaster Management Plan, a plan that suits the needs of the library. It also recommends training of the staff and the librarians on how to take care of the collection the government entrusted them with. The study used the IFLA (2007) guidelines to come up with a Proposed Disaster Management Plan for the Supreme Court Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Emergency management -- Philippines -- Manila; Philippines. Supreme Court Library